Prevalence of malnutrition and associated factors among children aged 6–24 months under poverty alleviation policy in Shanxi province, China: A cross-sectional study - Minli Zhang; Nelbon Giloi; Yang Shen; M. Y. Aza Sherin; Mei, Ching Lim (Elsevier Ltd, 2022)
Introduction: Child malnutrition continues to be a major public health issue, accounting for 54% of all child mortality globally. This study aimed to determine the prevalence of childhood malnutrition and its associated risk factors as well as to explore the best developmental strategy among infants and young children (IYC). Methodology: This cross-sectional study was conducted six months after the distribution of nutritious YingYangBao (YYB). It involved children aged 6–24 months in Shaanxi Province, China. Data were collected via interviews with parents of IYC, followed by measurements of the children’s height and weight. Data were analyzed using EpiInfo software and SPSSv.26, which encompassed descriptive statistics, Pearson Chi-square, and multivariate logistic regression analysis. Ethics approval and parents’ informed consent were attained prior to the study. Result: A total of 3431 data were analyzed in the study. The prevalence of stunting was highest among IYC between 12 and 18 months (3.9%). Prevalence of underweight (0.5%) and wasting (1.5%) were highest among IYC aged 18–24 months while the prevalence of overweight was highest among IYC aged 6–12months (9.0%). Significant associating risk factors of malnutrition were IYC from Northern Shaanxi (aOR = 2.24; 95% CI:1.68–2.98) and mothers with parity ≥3 (aOR = 1.52; 95%CI:1.10–2.10). IYC with a higher educated father (aOR = 0.79; 95%CI:0.66–0.95), YYB intervention (aOR = 0.77; 95%CI:0.65–0.90), correct supplementary food time (aOR = 0.84; 95%CI:0.71–1.00) and separate supplementary food preparation (aOR = 0.79; 95% CI:0.66–0.95) were significantly associated with lower risk of malnutrition. Conclusion: Even though the prevalence of stunting, underweight, and wasting were relatively low (<5%), there is still a need to strengthen existing policies on child nutrition.